EFEKTIVITAS EVALUASI PEMBELAJARAN BERBASIS HOTS MENGGUNAKAN KAHOOT PADA MATA PELAJARAN PAI DAN BUDI PEKERTI DI SDN 343 KUBANGAN TOMPEK - Elvi Silvia; Zainal Asril; Hidayati; Rivdya Eliza; Khadijah; Juliana Batubara; Musalwa (LP2M IAIN Sultan Amai Gorontalo, 2025)
Learning evaluation is the most important part of learning, because it measures the level of understanding of students of the material that has been delivered. Learning evaluations are still manual using paper and have not used digital platforms, such as kahoot. And the questions presented during the learning evaluation are not HOTS-based so that students are not accustomed to high level thinking (Critical Thinking). This study aims to improve the high-level thinking ability of students in grade VI SD 343 Kubangan Tompek and innovation in learning evaluation. This type of research is a quasi experiment using control and experimental classes. Quasi experimental method (Quasi Eksperiment). to obtain an overview of the improvement of students' learning outcomes. The results of this study are that HOTS-based learning evaluation using kahoot is effective enough to improve students' higher order thinking skills based on the N-gain scores of the experimental and control classes. The control class with an average value of 0.26 with a low category, then interpreted with a value of 26.77% with a description of less effective. In the experimental class with an average value of 64 with moderate criteria and interpreted by obtaining an average value of 64% with a fairly effective category. Evaluation of Higher Order Thinking Skills (HOTS) based learning using kahoot is quite effective.